1994
DOI: 10.1007/bf00548591
|View full text |Cite
|
Sign up to set email alerts
|

Role of diatoms as indicators of pollution gradients

Abstract: The impact of liquid wastes from a paper mill on the benthic diatoms in flowing waters has been studied for a period of two years. Water and algal samples were analysed at monthly intervals at three sites along the course of the river, along with raw effluents. The water before the confluence of effluents was well oxygenated with an alkaline pH. Organic matter, NH3 and nutrients were recorded at low concentrations. At the entry of effluents, the water showed considerable decline in dissolved oxygen content, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…TDS was another significant variable affecting the spatial pattern of benthic algae, which was negatively correlated with the third CCA axis (r = -0.509, P = 0.002). The study carried out by Sudhakar et al (1994) and Bate et al (2004) also found out TDS was an important factor for the distribution of diatom communities. In general, TDSs comprise inorganic salts (principally calcium, magnesium, potassium, sodium, bicarbonates, chlorides, and sulfates) and some small amounts of organic matter that are dissolved in water.…”
Section: Comparison Among Different Groupsmentioning
confidence: 88%
“…TDS was another significant variable affecting the spatial pattern of benthic algae, which was negatively correlated with the third CCA axis (r = -0.509, P = 0.002). The study carried out by Sudhakar et al (1994) and Bate et al (2004) also found out TDS was an important factor for the distribution of diatom communities. In general, TDSs comprise inorganic salts (principally calcium, magnesium, potassium, sodium, bicarbonates, chlorides, and sulfates) and some small amounts of organic matter that are dissolved in water.…”
Section: Comparison Among Different Groupsmentioning
confidence: 88%
“…These are very suitable organisms for the determination of the impact of toxic substances on the aquatic environment because any effect on the lower level of the food chain will also have consequence on the higher level (Joubert, 1980). Algae are used for assessing the degree of pollution or as indicator of water pollution of different water bodies (Trivedy, 1986;Sudhaker et al, 1994;Dwivedi and Pandey, 2002).…”
mentioning
confidence: 99%
“…They are the base of the food chain in open water bodies and also provide food for organisms that are higher in the trophic levels [4,5]. Phytoplankton play a critical role in primary production, nutrient cycling and food web, and are used in assessing the degree of pollution or as indicators of Pollution of different water bodies due to their very sensitive nature and response to changes in their environment [6][7][8]. In a fresh water bodies changes in phytoplankton community can result in changes in the fish production and the entire productivity of water, because once the community of plankton change by the effects of pollutants; the structure, stability and function of ecological system can be changed as well.…”
Section: Introductionmentioning
confidence: 99%